PENGARUH UNDANG-UNDANG ITE TERHADAP HUBUNGAN ANTARA MASYARAKAT DAN PEMERINTAH DI KOTA PADANGSIDIMPUAN - Khoiruddin Manahan Siregar (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This article describes the influence of the ITE Law on the relationship between the community and the government in Padangsidimpuan City. To determine the effect of public and government relations, the author uses a qualitative method, namely seeking information or data by directly interviewing the people of Padangsidimpuan City about the influence of the ITE Law on public relations with the government.The findings in the search, that the ITE Law is for the majority of the people of Padangsidimpuan City, that this ITE Law has a positive influence where people get accurate news, avoids hoax news and does not separate the community from the government, but a small part of the people of the City Padangsidimpuan argues that the presence of this ITE Law actually contains a dividing space between the government and the community where people are afraid to criticize the government through the internet.